Perbedaan NilaiArus Puncak Ekspirasi (APE) antara BuruhProses Pencelupan dengan Buruh Administrasi Industri Batik - Anisa Nur Rahma; . Harsini; . Muthmainah (Nexus Kedokteran Komunitas, 2014)
Background: One of the negative impactsof industy development is the occurance of occupational disease. The respiratory disease is one of the occupational disease that can cause lung disfunction. The function of lung can be observed by peak expiratory flow (PEF) value. The aim of this study is to know the difference on the percentage of measured PEF value compared with predictive PEF value, between immersion processing workers and administrative workers in batik industry. Methods: This study was an observational study with cross sectional design. Study was conducted in July-September 2013 in the batik industry in Laweyan District. Samples were taken by stratified random sampling. Samples that consisted of 60 workers were divided into two groups: 30 immersion processing workers and 30 administrative workers in batik industry. The measurement of PEF used the Peak Flow Meter. The measured PEF valuewas compared with the predictive PEF value and then expressed on percentage form. Data were analyzed using the Mann Whitney test (a=0.05). Result:This study showed the mean value of percentage of measured PEF compared with predictive PEF on administrative workers was 75,6% 8,7, the mean value of percentage of measured PEF compared with the predictive PEF on immersion processing workers was 62,9% 11,7. Mann-Whitney test showed that p=0.000 (p<0.005), so there was a significant difference between the value on the administration workers and the value on Immersion Processing Workers in Batik Industry. Conclusion:The percentage of measured PEF value compared with predictive PEF valueon administrative workers wassignificantly higher than the percentage of measured PEF value compared withpredictive PEF value on Immersion Processing Workers in Batik Industry. Keywords: Batik, PEF value, administration workers, Immersion Processing Workers in Batik Industry